The Study of Drying Kinetics of Uncaria Gambir Roxb Leaves Applying Convective Desiccant Drying - R. Anggraini, R. Sundari, R. Hasibuan, R. Manurung, S. Alva (International Journal of Advanced Science and Technology, 2020)
Uncaria gambir Roxb leaves as one of valuable herbals advantaged for cosmetics, painting, leather, pesticides, hormones and pharmaceutical products. This article is related to drying kinetics study of Uncaria gambir Roxb leaves corresponding with temperatures (35, 45, and 55oC) and air velocities (1.2, 2.3, and 3.6 m/s) using convective desiccant drying with silica gel desiccant and convective fan. The results show the reduction of moisture content of Uncaria gambir Roxb achieved to 4.3% (35oC and 1.2 m/s) after 270 min. drying that is lower than 10% as the threshold level. Significant reductions of moisture content are observed by 58% and 85% after 10 min. and 20 min. drying (55oC and 1.2 m/s), respectively. The favorable condition is obtained at 2.3 m/s after 60 min. drying at 35oC performs the highest drying rate. This study shows a two period drying characteristic at air velocity of 1.2 m/s (55oC), while a three period drying characteristic at air velocity of 3.6 m/s (35oC).